2014
DOI: 10.1111/area.12124
|View full text |Cite
|
Sign up to set email alerts
|

The ‘tiger of Indian rivers’: stakeholders' perspectives on the golden mahseer as a flagship fish species

Abstract: Promoting a fish as a flagship species (i.e. a charismatic animal that promotes awareness) is a management tool to improve the effectiveness of conservation measures. However, to be successful this approach requires strong stakeholder support. To investigate the feasibility of the flagship species approach and degree of stakeholder support in India, semi-structured interviews were conducted with forest managers, anglers and village members in Uttarakhand. Stakeholders were supportive of the flagship approach a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 33 publications
(56 reference statements)
0
28
0
Order By: Relevance
“…Social science surveys were conducted using a semi-structured interview approach (Gupta, Sivakumar, Mathur, & Chadwick, 2014). Their aim was to document local community knowledge, attitudes and perceptions regarding otters, including questions such as: Have otters been present in the past in your area?…”
Section: Social Science Surveysmentioning
confidence: 99%
“…Social science surveys were conducted using a semi-structured interview approach (Gupta, Sivakumar, Mathur, & Chadwick, 2014). Their aim was to document local community knowledge, attitudes and perceptions regarding otters, including questions such as: Have otters been present in the past in your area?…”
Section: Social Science Surveysmentioning
confidence: 99%
“…Interestingly, of the six recorded threatened species Table 2). This could be attributed to the observed migratory behaviour of this species (Gupta et al, 2014c). Further, terrestrial protected areas scored less for observed anthropogenic threats in comparison to managed reaches (see Table 3).…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, of the six recorded threatened species PARKS VOL 21.1 MARCH 2015 (IUCN, 2014), only one (T. putitora) was recorded both from the UNPR and PR sites of terrestrial protected areas and managed reaches (see Table 2). This could be attributed to the observed migratory behaviour of this species (Gupta et al, 2014c). Further, terrestrial protected areas scored less for observed anthropogenic threats in comparison to managed reaches (see Table 3).…”
Section: Discussionmentioning
confidence: 87%